Bamboo fiber improves piglet growth performance by regulating the microbial composition of lactating sows and their offspring piglets - Dai, Fawen; Lin, Tao; Jin, Muqu; Huang, Xia; Wang, Lu; Ma, Jing; Yu, Hang; Fan, Xianlin; Nong, Xiang; Zuo, Jianjun (Frontiers in Microbiology, 2024)
In this study, IDF-based rice mill feed and feeding bamboo powder were used to compare the effects of bamboo fiber on fecal microflora and performance of lactating sows and their offspring piglets. 30 healthy crossbred gilts at day 105 of gestation were randomly allocated into 3 groups: CON, TRE1 supplemented with 2% feeding bamboo powder (mainly composed of nature bamboo fiber) and TRE2 supplemented with 2% compound feeding bamboo powder (99% feeding bamboo powder +1% bamboo fiber polymer material). The results showed that: Compared with CON, the average feed intake of sows in TRE1 during the second week of lactation was significantly increased by 21.96% .The average daily gain of piglets on 11-21 d and 3-21 d of lactation was significantly increased by 43.75% and 30.18%, respectively. The serum triglyceride content of sows on the 2 21 st day of lactation was significantly increased. The 16S rRNA analysis showed that different fiber treatments had significant effects on fecal microbial richness index Ace, Chao and Sobs, and had a tendency to change Ace index of lactating piglets. Feeding stage had significant effects on fecal microbial richness index Ace, Chao and Sobs and microbial diversity index Shannon and Simpson in gilts and their suckling piglets. On the 7 th day after delivery, there were significant differences in the abundance ofChristensenellaceae_R-7_group among CON, TRE1 and TRE2 gilts. There was a trend of difference in Clostridium_sensu_stricto_1 among these gilts on day 21 after delivery . There was significant difference in Comamonas of suckling piglets among these groups. Spearman correlation analysis showed that the abundance of Phascolarctobacterium in feces of lactating piglets on d 21 was significantly positively correlated with diarrhea rate . It was significantly negatively correlated with 21-day litter weight, average daily gain and 3-21d survival rate . In contrast, the abundance of Christensenellaceae_R-7_group was significantly negatively correlated with diarrhea rate and positively correlated with litter average daily gain. These results indicated that 2% feeding bamboo powder supplementation improved the weight gain of suckling piglets, which was related to the improvement of dietary intake, lipid metabolism and microbial composition of sows and piglets.